An Efficient approach of True Random Number Generation using A Data encryption method in Security & cryptography algorithm - Agnihotri, Prateek; Agarwal Mittal, Preeti (2023 International Conference on IoT, Communication and Automation Technology (ICICAT), 2023)
True random number generators (TRNGs) have drawn a lot of focus due to their numerous uses in data encryption and transfer. The encryption method or privacy protocols of the data protection centre often use the real random numbers produced by the true random number generators. TRNGs were already being used to save energy in the recent times developed stochastic computing paradigm. This methodology utilizes the extended symmetric key cryptography technique, which utilizes the very same framework for both the encryption and decryption processes. The encryption and decryption keys used in traditional cryptography techniques are identical and are kept private. The technique employs a randomized numbers generator to generate keys, which increases technique performance. The algorithm uses 512-bit keys for increased security and offers the idea of intrinsic key creation at the receiving end using the 512-bit key provided by the transmitter. To avoid conventional warfare assaults as well as any damaging cyber threats, this private key will be stored in the transmitter side databases and sent to the side of the receiver in a different way. This approach performs encryption and decryption more effectively for huge information than previous techniques do. With huge documents with reduced latency, this technique offers a higher pace compared to previous methods.